2020
DOI: 10.1111/ijfs.14529
|View full text |Cite
|
Sign up to set email alerts
|

Effect of processing method on vitamin profile, antioxidant properties and total phenolic content of coconut (Cocos nucifera L.) sugar syrup

Abstract: Coconut (Cocos nucifera L.) sugar is a more nutritious alternative sugar source as compared to sugar palm (Borassus flabellifer) and sugarcane (Saccharum officinarum L.). This work was aimed to investigate the browning index (BI), vitamin profile and antioxidant properties of coconut sap sugar syrups, which were produced by different processing methods: rotary evaporation (RE), microwave evaporation (ME) and open-heat evaporation (OHE). The results obtained showed that coconut sugar syrup produced by RE-60 con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 29 publications
0
10
0
1
Order By: Relevance
“…In addition, different processing methods can also affect the sugar profiles. Previous studies have shown that several methods conducted on coconut sap, such as rotary evaporation and microwave, resulted in different sugar profiles and physicochemical properties (Asghar et al ., 2020c,b).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, different processing methods can also affect the sugar profiles. Previous studies have shown that several methods conducted on coconut sap, such as rotary evaporation and microwave, resulted in different sugar profiles and physicochemical properties (Asghar et al ., 2020c,b).…”
Section: Introductionmentioning
confidence: 99%
“…Ash content reports as 620 mg per 100g of sap and it indicates the considerable amount of minerals present in the fresh sap which may lead to producing palm sugar with minerals (Table 3). Studies show that the pH of the fresh Kithul sap is 5.7-5.8 [5] whereas the pH of coconut sap is in the range of 5.71 [16].…”
Section: Resultsmentioning
confidence: 99%
“…The degree of the browning development was governed by several factors, especially temperature–time regime and types, concentration and ratio of reactants (Ajandouz et al ., 2001; Ajandouz et al ., 2008). The Maillard reaction is correlated well with the reaction temperature and time (Teodorowicz et al ., 2018; Asghar et al ., 2020b).…”
Section: Resultsmentioning
confidence: 99%
“…However, thermal Maillard reaction had a detrimental effect on the colour of the final syrup because dark syrup could be rejected by consumers (Jiang et al ., 2013). The production of MRPs could be enhanced at a higher processing temperature and a prolonged processing time as found in the production of coconut ( Cocos nucifera L.) sugar syrup (Asghar et al ., 2020b). Thus, the use of a mild condition to facilitate the glycation between added amino acid and endogenous reducing sugar in syrup is of great interest.…”
Section: Introductionmentioning
confidence: 99%